Suicide and Self-Harm in Recent Immigrants in Ontario, Canada: A Population-Based Study. (November 2019) - Saunders, Natasha Ruth; Chiu, Maria; Lebenbaum, Michael; Chen, Simon; Kurdyak, Paul; Guttmann, Astrid; Vigod, Simone
Objective: To estimate the rates of suicide and self-harm among recent immigrants and to determine which immigrant-specific risk factors are associated with these outcomes. Methods: Population-based cohort study using linked health administrative data sets (2003 to 2017) in Ontario, Canada which included adults ≥18 years, living in Ontario ( N = 9, 055, 079). The main exposure was immigrant status (long-term resident vs. recent immigrant). Immigrant-specific exposures included visa class and country of origin. Outcome measures were death by suicide or emergency department visit for self-harm. Cox proportional hazards estimated adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs). Results: We included 590, 289 recent immigrants and 8, 464, 790 long-term residents. Suicide rates were lower among immigrants ( n = 130 suicides, 3.3/100, 000) than long-term residents ( n = 6, 354 suicides, 11.8/100, 000) with aHR 0.3, 95% CI, 0.2 to 0.3. Male–female ratios in suicide rates were attenuated in immigrants. Refugees had 2.1 (95% CI, 1.3 to 3.6; rate 6.1/100, 000) and 2.8 (95% CI, 2.5 to 3.2) times the likelihood of suicide and self-harm, respectively, compared with nonrefugee immigrants. Self-harm rate was lower among immigrants ( n = 2, 256 events, 4.4/10, 000) than long-term residents ( n = 68, 039 events, 9.7/10, 000 person-years; aHR 0.3; 95% CI, 0.3 to 0.3). Unlike long-term residents, where low income was associated with high suicide rates, income was not associated with suicide among immigrants and there was an attenuated income gradient for self-harm. Country of origin-specific analyses showed wide ranges in suicide rates (1.4 to 9.9/100, 000) and self-harm (1.8 to 14.9/10, 000). Conclusion: Recent immigrants have lower rates of suicide and self-harm and different sociodemographic predictors compared with long-term residents. Analysis of contextual factors including immigrant class, origin, and destination should be considered for all immigrant suicide risk assessment.